Modern Approaches To Protecting Students And Youth From Information Threat - Asomiddin Xudayberdiyev (Periodica Journal, 2023)
Today's global information process is reflected in all spheres of public development. Eto trebuet bditelnosti i formirovaniya kultury ispolzovaniya informatsii pri otbore, sortirovke informatsii i reagirovanii na nee. This allows a critical approach to information and global networks, which is most important, to apply information, knowledge and own scientific data. Indeed, at present, the active layer of young people is students, and in their worldview it is vain to cultivate the spirit of patriotism, a sense of belonging to the future of the country.
Keywords: information process,; spirit of patriotism